2004
DOI: 10.1111/j.1472-765x.2004.01596.x
|View full text |Cite
|
Sign up to set email alerts
|

A real-time polymerase chain reaction-based method for rapid and specific detection of spoilage Alicyclobacillus spp. in apple juice

Abstract: Aims: To develop a real-time PCR-based rapid detection method for spoilage Alicyclobacillus spp. in juice products. Methods and Results:The squalene-hopene cyclase-encoding gene was targeted for primer-and-probe development. Gene fragments from representative strains were cloned, and PCR primers and probe were designed by DNA sequence comparison. Selected bacteria were examined for cross-reactivity by the new method. Cells were serially diluted in apple juice and saline, and examined by the new method to estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 33 publications
(50 reference statements)
0
28
0
Order By: Relevance
“…Few rapid, molecular-based detection methods targeting spore-forming bacteria responsible for food spoilage have been developed (9,22,24), and of these, none have focused on Paenibacillus, the psychrotolerant spore-forming genus associated with dairy spoilage. The absence of appropriate tools may reflect, in part, the fact that the bacterial ecology of pasteurized fluid milk has only recently been characterized at the molecular level, which led to identification of Paenibacillus as the predominant fluid milk spore-forming spoilage genera (12,19,21,34).…”
Section: Discussionmentioning
confidence: 99%
“…Few rapid, molecular-based detection methods targeting spore-forming bacteria responsible for food spoilage have been developed (9,22,24), and of these, none have focused on Paenibacillus, the psychrotolerant spore-forming genus associated with dairy spoilage. The absence of appropriate tools may reflect, in part, the fact that the bacterial ecology of pasteurized fluid milk has only recently been characterized at the molecular level, which led to identification of Paenibacillus as the predominant fluid milk spore-forming spoilage genera (12,19,21,34).…”
Section: Discussionmentioning
confidence: 99%
“…Ten out of 13 samples (77%) showed background contamination of the genus Alicyclobacillus, while 7 out of the 13 samples (54%) showed the specific presence of A. acidoterrestris background contamination (Table 1). A number of reports have shown that A. acidoterrestris can be present in both fresh juices and juice concentrates (Pettipher et al 1997;Luo et al, 2004;Groenewald et al 2009;Groenewald et al 2013;McKnight et al, 2010;Wang et al, 2013). The presence of background Alicyclobacillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…spoilage is a global problem in the fruit juice industry (Cagnasso et al 2010;Groenewald et al 2009, McKnight et al 2010, Walls & Chuyate 2000. Most instances of contamination have been reported in apple and orange juices (McKnight et al, 2010;Groenewald et al, 2009;Luo et al 2004). In the US juice industry alone, Alicyclobacillus spp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations